A nonlinear dynamic model for 2D deepwater steel lazy-wave riser subjected to top–end imposed excitations. (3rd April 2018) - Wang, Jinlong; Duan, Menglan; He, Renyang
ABSTRACT: Deepwater steel lazy-wave riser (SLWR) has won more and more applications in deepwater oil and gas resources development. The dynamic response induced by the wave, ocean current, ship motion, internal flow and other factors in operation phase has been highly concerned by researchers and engineers. A 2D nonlinear dynamic model for SLWR based on Euler–Bernoulli beam theory with initial conditions and boundary conditions under top excitations considering the effect of ocean current and internal flow is proposed. Keller Box finite difference scheme is adopted to solve the partial differential equations. Numerical analysis is conducted to investigate the influences of tangential and normal excitations on the riser's dynamic response. The proposed model can be a basic reference for the design and analysis for deepwater SLWR.